PENGEMBANGAN MODUL PRAKTEK INSTALASI LISTRIK DOMESTIK BERBASIS PROYEK UNTUK MAHASISWA TEKNIK LISTRIK - Fornando, Yusuf; Sukardi, Sukardi; Ahyanuardi, Ahyanuardi (Universitas Negeri Padang, 2020)
Based from observation of the learning process of the Domestic Electrical Installation Practice of vocational students of the Electrical Engineering Study Program, Faculty of Engineering, Padang State University shows that the learning process is not optimal because of practical learning unchallenged students to be creative in planning and implementing Domestic Electrical Installation Practices. The research objective is to develop a project-based practice module that can improve student learning outcomes in the learning process of the Domestic Electrical Installation Practice. Research with Four-D design is applied to develop and test the validity, practicality, and effectiveness of project-based practice modules in learning domestic electrical installation practices. The stages of the research include defining, designing, developing, and distributing. The results of testing the validity of project-based practices indicate that the learning media is valid. These aspects are material, media aspects, and language aspects. Indicates that the project-based practice module is valid to apply in the learning process of Domestic Electrical Installation Practices. The result the data analysis shows that the practice module developed in the Domestic Electrical Installation Practice learning process is valid, it can be concluded that the project-based practice module is valid for use in the learning process Domestic Electrical Installation for Electrical Engineering Study Program students.